Perspectives of Digital Health Innovations in Low- and Middle-Income Health Care Systems From South and Southeast Asia - Yi, Siyan; Yam, Esabelle Lo Yan; Cheruvettolil, Kochukoshy; Linos, Eleni; Gupta, Anshika; Palaniappan, Latha; Rajeshuni, Nitya; Vaska, Kiran Gopal; Schulman, Kevin; Eggleston, Karen N (Journal of medical Internet research, 2024)
Digital health innovations have emerged globally as a transformative force for addressing health system challenges, particularly in resource-constrained settings. The COVID-19 pandemic underscored the critical importance of these innovations for enhancing public health. In South and Southeast Asia, a region known for its cultural diversity and complex health care landscape, digital health innovations present a dynamic interplay of challenges and opportunities. We advocate for ongoing research built into system development and an evidence-based strategy focusing on designing and scaling national digital health infrastructures combined with a vibrant ecosystem or “marketplace” of local experiments generating shared experience about what works in which settings. As the global digital health revolution unfolds, the perspectives drawn from South and Southeast Asia—including the importance of local partnerships—may provide valuable insights for shaping future strategies and informing similar initiatives in low- and middle-income countries, contributing to effective digital health strategies across diverse global health contexts.